Value of Ki-67 Labeling Index in Predicting Recurrence of WHO Grade I Cranial Base Meningiomas - Matias, Jose Gabrielle; Jusue-Torres, Ignacio; Martin, Brendan; Bajaj, Ankush; Borys, Ewa; Melian, Edward; Barton, Kevin; Anderson, Douglas E.; Prabhu, Vikram C. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Assess impact of Ki-67 labeling index (LI; Ki-67 LI) on risk of recurrence or progression of WHO grade I meningiomas.Study Design Retrospective study of adult patients who underwent resection of cranial base meningioma between 2004 and 2016.Results 272 patients fulfilled criteria for inclusion in the study. Average age was 61.8 years; 196 (72%) were females. Simpson's grade 1 resection was noted in 77 patients (32%), grade 2 in 39 (16%), grade 3 in 36 (15%), and grade 4 in 88 (37%). The Ki-67 LI was low (1–4%) in 214 (78.7%), intermediate (5–9%) in 44 (16.2%), and high (>10%) in 14 (5.2%). Median follow-up was 39 months (IQR: 16–71 months); 221 (87.1%) tumors remained stable or did not recur, 19 (7.4%) recurred, and 14 (5.5%) progressed. Compared with tumors with low Ki-67 LI, those with intermediate Ki-67 LI had 2.47 times (2.47 [1.09–5.59], p = 0.03), and those with high Ki-67 LI had 3.38 times (3.38 [1.16–9.89], p = 0.03) higher risk of recurrence or progression. Tumors with Ki-67 LI > 4% had a shorter time to recurrence or progression (p = 0.01). Recurrence or progression-free survival rates at 3, 5, and 10 years for tumors with low Ki-67 LI were 95%, 89%, and 75%, respectively; tumors with intermediate Ki-67 LI, 87%, 69%, and 52%, respectively; tumors with high Ki-67 LI, 78%, 49%, and 49%, respectively.Conclusions Following surgical resection of a WHO grade I cranial base meningioma, Ki-67 LI > 4% may predict an increased risk of recurrence or progression of residual tumor.
Keywords: meningioma; cranial base meningioma; meningioma recurrence; Ki-67 labeling index